Lipid and carotenoid production by a Rhodosporidium toruloides and Tetradesmus obliquus mixed culture using primary brewery wastewater supplemented with sugarcane molasses and urea - Dias, Carla (2022)
ABSTRACT: In this study, Rhodosporidium toruloides and Tetradesmus obliquus were used for lipid and carotenoid production in mixed cultures using primary brewery wastewater (PBWW) as a culture medium, supplemented with sugarcane molasses (SCM) as a carbon source and urea as a nitrogen source. To improve biomass, lipid, and carotenoid production by R. toruloides and T obliquus mixed cultures, initial SCM concentrations ranging from 10 to 280 g L-1 were tested. The medium that allowed higher lipid content (26.2% w/w dry cell weight (DCW)) and higher carotenoid productivity (10.47 mu g L-1 h(-1)) was the PBWW medium supplemented with 100 g L-1 of SCM and 2 g L-1 of urea, which was further used in the fed-batch mixed cultivation performed in a 7-L bioreactor. A maximum biomass concentration of 58.6 g L-1 and maximum lipid content of 31.2% w/w DCW were obtained in the fed-batch cultivation. PBWW supplemented with SCM was successfully used as a low-cost medium to produce lipids and carotenoids in a R. toruloides and T obliquus mixed culture, with higher productivities than in pure cultures, which can significantly reduce the cost of the biofuels obtained.